Unique cellular interactions between pancreatic cancer cells and the omentum. - Valerya Feygenzon; Shelly Loewenstein; Nir Lubezky; Metsada Pasmanic-Chor; Osnat Sher; Joseph M Klausner; Guy Lahat (PLoS ONE)
Pancreatic cancer is a common cause of cancer-related mortality. Omental spread is frequent and usually represents an ominous event, leading to patient death. Omental metastasis has been studied in ovarian cancer, but data on its role in pancreatic cancer are relatively scarce and the molecular biology of this process has yet to be explored. We prepared tissue explants from human omental fat, and used conditioned medium from the explants for various in vitro and in vivo experiments designed to evaluate pancreatic cancer development, growth, and survival. Mass spectrometry identified the fat secretome, and mRNA array identified specific fat-induced molecular alternations in tumor cells. Omental fat increased pancreatic cancer cellular growth, migration, invasion, and chemoresistance. We identified diverse potential molecules secreted by the omentum, which are associated with various pro-tumorigenic biological processes. Our mRNA array identified specific omental-induced molecular alternations that are associated with cancer progression and metastasis. Omental fat increased the expression of transcription factors, mRNA of extracellular matrix proteins, and adhesion molecules. In support with our in vitro data, in vivo experiments demonstrated an increased pancreatic cancer tumor growth rate of PANC-1 cells co-cultured for 24 hours with human omental fat conditioned medium. Our results provide novel data on the role of omental tissue in omental metastases of pancreatic cancer. They imply that omental fat secreted factors induce cellular reprogramming of pancreatic cancer cells, resulting in increased tumor aggressiveness. Understanding the mechanisms of omental metastases may enable us to discover new potential targets for therapy.